PENEGAKAN HUKUM LALU LINTAS JALAN SECARA ELEKTRONIK SEBAGAI WUJUD PEMBANGUNAN HUKUM WILAYAH HUKUM JAKARTA SELATAN - Sekar Putri Nindyaningrum; Gayo, Sabela; Hakim, Lukman (Veteran Law Review, 2023)
This research will focus on discussing the use of ETLE technology in the digital era in optimizing law enforcement in the traffic sector in order to reduce the number of traffic violations that occur today. Through the use of ETLE technology, it will be easier for the Traffic Unit to carry out its duties in the traffic field. The research method used is empirical juridical legal research. The research is descriptive analytical. The results showed that the problem in this study refers to the number of traffic violations that occurred in Indonesia in 2022, especially in the South Jakarta Legal Area. It was recorded that in 2022, the prosecution of traffic violations amounted to 57,756, compared to 29,349 in 2021. Although traffic law arrangements have been updated, there are still many traffic violations that occur. In the implementation of ETLE at the South Jakarta Metro Police, it has proven effective in catching traffic violators, but there are several obstacles in its implementation. Such as the weakness of the E-TLE camera, besides that the ticket sanctions are also not on target where the ETLE work mechanism raises the possibility that traffic violators are not motor vehicle owners, while the ticket will be sent with the database of motor vehicle owners in the motor vehicle registration and identification database.